Sustainable universities: the role of accounting, management and ESG - Lima, Clayton dos Santos; Degenhart , Larissa; Gavira, Muriel de Oliveira; Ávila, Lucas Veiga; Cavalcante, Diego Marques; Kieling, Débora Londero (Revista de Administração da UFSM, 2026)
Purpose: This study aims to examine how accounting, management, and Environmental, Social, and Governance (ESG) practices influence the sustainability strategies of universities listed in the Green Metrics ranking. Methodology: A quantitative approach was conducted with 106 Higher Education Institutions (HEIs) included in the ranking. The data collection instrument was developed through methodological triangulation, combining a Systematic Literature Review (SLR), analysis of institutional reports, and a structured questionnaire validated by experts. This design enabled the identification of impact studies and key sustainable practices already implemented in HEIs. Findings: The analysis revealed the main variables adopted by ranked institutions, the critical factors that foster sustainability and stakeholder engagement, and the correlations that highlight the role of planning in advancing sustainable development.